Analisis Strategi Lingkungan Pemasaran Global Terhadap Potensi Wisata Pantai Kuta Bali Dalam Menarik Wisatawan Mancanegara - Suhairi Suhairi; Amelia Putri; Liska Febrianti; Revika Viola Azzahara; Rifki Akmal Tanjung (Universitas Muhammadiyah Enrekang, 2022)
This study aims to analyze how the strategies adopted to create sustainable tourism on the motivation and behavior of tourists can affect the global marketing at Kuta Beach Bali that will be carried out. Sustainable tourism consists of environmental dimensions, economic dimensions, socio-cultural dimensions, and tourist satisfaction levels. This study uses a descriptive method, namely by looking at previous research and tourist data from several previous years. Whether the presence of tourists can facilitate the development of global marketing, we estimate the strategy we will take to attract tourists. Data collection is done through documentation. The results of the study show that Bali Kuta Beach Tourism has the potential and opportunities to develop tourism products that are more attractive to tourists in addition to tourism activities such as excursions and snorkeling. The tourism product in question is in the form of special interest tourism which has activities that can be packaged into tour packages.